Design Of Enterprise Architecture Of FEAF Standards On The Academic Information System Based On Website - Fahmi, Irwan (AI Society & STMIK Indonesia, 2025)
Academic Information System (SIAKAD) is a crucial element in supporting efficiency and effectiveness academic data management in educational institutions. Research This aims To analyze and apply Federal Enterprise Architecture Framework (FEAF) standards on designing Information Systems Academics at MA Bumi The Kingdom by using a website-based platform. FEAF was chosen as framework Work To ensure integration, interoperability, and sustainability of SIAKAD. Methods study This involves analysis of user needs, business process identification, and data modeling. The implementation of FEAF is integrated in stage design system, combining aspects such as business, data, applications, and technology architecture. The results of the study show that Application of FEAF in Information Systems MA Bumi Academic The Kingdom gives clarity supporting structure planning, development and maintenance of systems in a more systematic way. Implementation website based provides greater accessibility good and more interactive user experience. The application of FEAF also allows more good alignment between business needs and information technology, as well as increasing the system's adaptation ability to change environmental education. Success project This shows that implementation of the FEAF standard can become a strong foundation for designing Information Systems Sustainable and responsive academics in the formal education environment such as MA Bumi Persada. This research makes an important contribution in developing information systems that can increase efficiency and quality academic data management in educational institutions.